2016
DOI: 10.1080/00015458.2016.1147235
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide in orthopaedic surgery – is it worth the risk?

Abstract: Hydrogen peroxide (HO) is commonly used in orthopaedic surgery during cemented arthroplasty and wound washouts. Its purported roles include antisepsis, haemostasis, mechanical debridement, and optimising the cement-bone interface during cementing. However, despite its apparent harmless mechanism of action, HO has been implicated in fatal and near fatal complications caused through oxygen emboli. We present a case of oxygen embolism and review the existing literature to highlight its potential risks and its lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…The former interface however is not affected by hydrogen peroxide use, as by this point in the operation, the hydrogen peroxide solution will have already been used and washed away. Only the cement–bone fixation is strengthened by hydrogen peroxide, aligning with other similar studies, such as an in vitro tensile loading study that achieved better cement fixation when using hydrogen peroxide compared to using normal saline or povidone iodine ( Ackland et al 2009 , Yang et al 2016 ). In conjunction with specific techniques, hydrogen peroxide may show synergy with other antiseptics, such as chlorhexidine and dilute povidone-iodine ( Flemming et al 2016 ).…”
Section: Uses Of Hydrogen Peroxide In Hip Arthroplastiessupporting
confidence: 79%
See 2 more Smart Citations
“…The former interface however is not affected by hydrogen peroxide use, as by this point in the operation, the hydrogen peroxide solution will have already been used and washed away. Only the cement–bone fixation is strengthened by hydrogen peroxide, aligning with other similar studies, such as an in vitro tensile loading study that achieved better cement fixation when using hydrogen peroxide compared to using normal saline or povidone iodine ( Ackland et al 2009 , Yang et al 2016 ). In conjunction with specific techniques, hydrogen peroxide may show synergy with other antiseptics, such as chlorhexidine and dilute povidone-iodine ( Flemming et al 2016 ).…”
Section: Uses Of Hydrogen Peroxide In Hip Arthroplastiessupporting
confidence: 79%
“…As an irrigating solution with effervescence, hydrogen peroxide can mechanically remove tissue debris such as fat, blood and marrow from surface interstices and bony microstructures, which can also increase bony trabeculae porosity ( Ackland et al 2009 , Yang et al 2016 ). This debris removal is also important for preventing infections.…”
Section: Uses Of Hydrogen Peroxide In Hip Arthroplastiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of hydrogen peroxide in closed cavities is thought to pose a higher risk of oxygen embolus, instances of oxygen embolus have been reported in many other circumstances, including in vascular, 10 orthopaedic, 13 and spinal surgery. 8 In neurosurgery, in addition to systemic oxygen embolus, the use of hydrogen peroxide has resulted in direct neural toxicity, cerebral infarction, and tension pnemocephalus.…”
Section: Declaration Of Interestmentioning
confidence: 99%
“…Based on this limited set of data, there is currently no supportive evidence to recommend H 2 O 2 in the treatment of WON. Moreover, its safety is questionable because several case series reported that its use may be related to embolic events [ 47 52 ]. In conclusion, irrigation with H 2 O 2 is currently not advised.…”
Section: Introductionmentioning
confidence: 99%